Probable deinonychosaur tracks from the Upper Cretaceous Wapiti Formation (upper Campanian) of Alberta, Canada. (23rd June 2021) - Enriquez, Nathan J.; Campione, Nicolás E.; Sullivan, Corwin; Vavrek, Matthew; Sissons, Robin L.; White, Matt A.; Bell, Phil R.
Abstract: Late Cretaceous tracks attributable to deinonychosaurs in North America are rare, with only one occurrence of Menglongipus from Alaska and two possible, but indeterminate, occurrences reported from Mexico. Here we describe the first probable deinonychosaur tracks from Canada: a possible trackway and one isolated track on a single horizon from the Upper Cretaceous Wapiti Formation (upper Campanian) near Grande Prairie in Alberta. The presence of a relatively short digit IV differentiates these from argued dromaeosaurid tracks, suggesting the trackmaker was more likely a troodontid. Other noted characteristics of the Wapiti specimens include a rounded heel margin, the absence of a digit II proximal pad impression, and a broad, elliptical digit III. Monodactyl tracks occur in association with the didactyl tracks, mirroring similar discoveries from the Early Cretaceous Epoch of China, providing additional support for their interpretation as deinonychosaurian traces. Although we refrain from assigning the new Wapiti specimens to any ichnotaxon because of their relatively poor undertrack preservation, this discovery is an important addition to the deinonychosaur track record; it helps to fill a poorly represented geographic and temporal window in their known distribution, and demonstrates the presence of a greater North American deinonychosaur ichnodiversity than has previously been recognized.